Pushing the Boundaries of Amnesia and Myopia: A Critical Review of the Literature on Identity in Management and Organization Studies. (July 2017) - Knights, David; Clarke, Caroline
Abstract: The aim of this article is to review a selection of the literature on identity at work in Management and Organization Studies (MOS) in order to raise critical questions concerning what we see as the dangers of a certain amnesia and myopia. Insofar as some of the contemporary literature neglects to engage with the historical and multidisciplinary past and present, there is a tendency to leave common‐sense understandings of identity unexamined, thereby reproducing everyday preoccupations with securing the self. By contrast with such rational individualism, we seek a more embodied understanding of identity, where it is a means of building our ethical engagements and capacities for community living. By failing to problematize identity, there is little recognition of how attempts to secure the self are invariably self‐defeating if only because they are necessarily contingent on the other who is unpredictable and uncontrollable. The main contribution of the article is to show how this failure to interrogate identity is far from benign since it often results in reinforcing everyday preoccupations with the self that can turn into narcissism, and deflect and curtail alternative practices of embodied engagement. We trust that our deliberations will be helpful in advancing the 'road less travelled', where studies advance beyond taking identity for granted, and move instead towards more embodied understandings of ethical engagement.